PELAKSAAN PENETAPAN NILAI LIMIT PADA OBJEK LELANG HAK TANGGUNGAN OLEH PT. BANK MANDIRI, TBK BUSINESS BANKING CENTER PEKANBARU - Sinaga, Butet Tiara; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Auction activities are sales that offer prices that are getting lower or lower.Auction is considered as the main way to resolve problem loans. The definition ofthe auction is contained in Article 1 of Decree of the Minister of Finance Number27 / PMK.06 / 2016 Regarding the Bidding Implementation Guideline whichstates that: reach the highest price, which is preceded by an auctionannouncement.